TINJAUAN AKSIOLOGI PADA PROFIL PELAJAR PANCASILA KURIKULUM MERDEKA BELAJAR - Winda Trisnawati; Randi Eka Putra; Levandra Balti (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This research observed aspects of the philosophy of science that focuses on the axiological aspect (use value) of the profile of Pancasila student in the independent learning curriculum. The study used a qualitative research method with a literature study approach. The collection of relevant data information was taken from various library sources such as; books, journals, news, internet in accordance with the topic of discussion. The results of this study were obtained by classifying the dimensions, elements, and sub-elements of the Pancasila student profile of the independent learning curriculum into three categories of ethical components in philosophical axiology. It was found that there are three dimensions that contain descriptive ethics; there are four dimensions that contain normative ethics; and there are three dimensions that contain meta-ethical ethics.